Rancangan Data Warehouse Untuk Penunjang Sistem Informasi Eksekutif Pada Yayasan Ummu’l Quro di Depok - Khairi Fadli Winata; Dedek Indra Gunawan (International Forum of Researchers and Lecturers, 2024)
The progression of the technology that is growing rapidly so as to give various concessions in every aspect of life .In an age of globalization business competition that is more strict , both in industry of providing goods and services , the success of an enterprise or organization is very dependent on technology information that can be provided a report on for an analysis .The reporting system considered static inflexible in exploring information in a system information to .Dynamic reporting instrument necessary so users can do data analysis to see the available data of various dimensions .The methodology that was used is to build data application the warehouse used the top down .The result of this is the creation of a truly peneliltian base data and it can be applied that can be used to do analysis on key aspects of information transaksional that occurs in units of education at the foundation ummu l quro depok one used as a support ktaking process The decision by the leader